UNIFAC Evaluation of the quinary liquid-liquid phase equilibrium: Carboxylic acid - peroxy carboxylic acid - hydrogen peroxide - water - organic solvent - Brandolin, Salvador Eduardo; Scilipoti, José Antonio; Andreatta, Alfonsina Ester; Magario, Ivana (Journal of Chemical & Engineering Data)
Carboxylic peroxy acids are organic oxidants of relevance in the cosmetic, food, and agrochemical industries, used as intermediaries in the Baeyer-Villiger reaction and the Prileschajew epoxidation. The peroxy acids synthesis (peracidation) consists of a reversible reaction between a carboxylic acid and a hydrogen peroxide molecule to give a peroxy acid and water. This reaction is usually carried out in situ in a two-liquid-phase system (liq-liq): a continuous organic phase, in which the substrates to be epoxidized are dissolved, and a disperse phase of aqueous nature, as a supply of hydrogen peroxide molecules. The nonideality and dynamic character of reactive biphasic systems entails the difficulty in the estimation of the distribution of species between both phases, which in turn determines its kinetic description. Then, a thermodynamic model that describes the phase behavior, with acceptable precision, is required. Therefore, the aim of this work was to evaluate the UNIFAC model's performance to predict the phase distribution of peroxy carboxylic acid, carboxylic acid, and hydrogen peroxide through nonreacting as well as reacting systems. The immobilized lipase from Candida antarctica B was used as the catalyst of the reaction. The systems also varied according to the type of carboxylic acids used -(lauric, octanoic, or acetic) and the type of solvent used (diisopropyl ether, toluene, hexane, or heptane). UNIFAC showed suitable estimations of some of the component solubilities, especially with toluene systems, presenting some limitations in the description of interactions of asymmetric compounds such as hydrogen peroxide and hexane. Fil: Brandolin, Salvador Eduardo. Universidad Nacional de Córdoba. Instituto de Investigación y Desarrollo en Ingeniería de Procesos y Química Aplicada. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Córdoba. Instituto de Investigación y Desarrollo en Ingeniería de Procesos y Química Aplicada; Argentina Fil: Scilipoti, José ...